Gera-Stone: Development of Renewable Ceramic Media for Quality Enhancement and Product Diversification of Pundong Potter - Arif Suharson; Joko Subiharto; Dwita Anja Asmara; Dyah Retno Fitriani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
Traditional pottery centers in Indonesian face challenges related to declining material quality, limited finishing techniques, and low market competitiveness. The Pundong pottery center in Bantul Regency, Yogyakarta, reflects this condition, where products are generally limited to low-fired bisque wares with low functional and economic value. This research aims to develop and evaluate GERA-STONE, a hybrid ceramic material combining local earthenware clay with stoneware to improve product quality and market acceptance. The study employed a participatory research and development (R&D) approach integrated with practice-based research, involving 30 artisans. The research was conducted in three stages: material development, finishing exploration, and product evaluation through direct market testing in a public exhibition. Data were collected through observation, experimentation, discussions, and market testing, and analyzed descriptively. The results show that GERA-STONE improves structural stability, firing performance, and glaze compatibility. Finishing techniques enhance both aesthetic and functional qualities, enabling products to serve as tableware and home décor. Market testing indicates positive consumer responses, with products achieving prices 300–500% higher than conventional pottery. These findings confirm that innovation in material and technique, supported by participatory processes and market evaluation, can significantly enhance product quality and economic value.